Constant‐frequency shoot‐through sine pulse‐width‐modulation scheme for three‐phase single‐input–hybrid‐output converter. Issue 9 (1st July 2016) - Ray, Olive; Mishra, Santanu
Abstract : Single‐input–hybrid‐output converters provide dc and ac outputs simultaneously from a single dc source in an integrated architecture. These topologies are well suited for applications comprising both dc and ac distribution buses. In this work, the three‐phase boost‐derived hybrid converter (3‐ φ BDHC) has been studied which provides a 3‐ φ ac output in addition to the step‐up output obtained from a boost converter. The changes in design and the characteristic behaviour of the proposed BDHC topology have been studied in comparison to single‐phase BDHC. The pulse‐width‐modulation (PWM) control associated with these topologies involves shoot‐through states incorporated within the conventional sine‐PWM strategies. The work proposes a PWM switching strategy with controllable shoot‐through occurring at constant frequency to achieve lower inductor current ripple. The operating principle of the 3‐ φ BDHC under balanced‐load conditions using the proposed constant‐frequency shoot‐through sine PWM has been validated using experimental results.